Lutero y educación: fundamento y distinción para la escuela luterana - Rautenberg, Cristian Eldor (2009)
This research s work presents, as result, the theological-pedagogical proposal that arises from the analysis of writings of Martin Luther. The reformer responds to his historical context on educational matters, reason why a general picture of the educative system situation in the Middle Age is displayed and also antecedents of the Lutheran Reformation and biographical details of the Martin Luther s life. It emphasizes aspects that got to be referential for the educative proposals of the reformer. Having been established the historical subjects of the Reformation s time; and understood the situation of the educative system and its methods, research s focus is put on theological Lutheran concepts that influence the pedagogical proposals of the reformer. Concepts coming from a Luther that being pastor and theologian acts responding to specific situations and elementary questions. The Luther s thought about education is marked for his understanding of the relationship between God and the human being and, at the same time, of this with the World and society. Doctrines as Justification by faith, the right place of the Good Works, Law and Gospel and the Two Kingdoms are essentials in the understanding of his thought about the right place of the education and the human being as its subject. Study and analysis continues being centered on pedagogical principles for a Lutheran education, as consequence of the reflection on pedagogical writings of the reformer, bibliographical research and other Lutheran theological writings as well. Pedagogical thought of Luther, as well as its relation with the humanism in the education is developed as result. Finally a pedagogical proposal for the Lutheran school is presented and it service to the Gospel and the world is highlighted. In last instance, the present work concludes that the Lutheran education foundation is on the Word of God and that the mark of the Lutheran school is in the instruction and christian education. It is the axis of all its structure, preoccupation and educative task.